Penegakan Hukum Lingkungan Atas Pembuangan Limbah Plastik Di Indonesia - Vianka, Maria Ibella (MORALITY: Jurnal Ilmu Hukum; Vol 7 No 2 (2021): Morality :Jurnal Ilmu Hukum, 2021)
Indonesia is the second largest contributor to plastic waste after China. It was found, as much as 187.2 tons of garbage pooled in Indonesian seas. Plastic waste in the oceans threatens marine biota ecosystems and human life. Prediction that in the coming year, more human food sources will be contributed from the sea. This problem needs to be the main point of the state in terms of preventing environmental damage. The State of Indonesia has regulated the oldest environment in the PPLH Law. In preventing these problems, it is necessary to carry out surveillance efforts by law enforcement officers in the community. However, supervision efforts in the field as a preventive measure are not carried out optimally, the sanctions applied are not firm, making the community and business actors not heed the legal rules that have been made. Enforcement of environmental law is carried out with three legal instruments, namely administrative sanctions, civil matters and criminal matters. Reflecting on developed countries, such as the neighboring country of Singapore, Indonesia should apply the rule of law strictly, considering that efforts to protect the environment are fundamental to making the country in it a comfortable place. In protecting the environment of the State of Indonesia, the government should act decisively in enforcing the law and implementing new legal rules, namely in the form of fines that can be applied to the community and should be the main priority of the state to keep the country free from plastic waste in the oceans.